Oral administration of ethanol extract from Gynura procumbens stems corrects kidney injury and renal anemia in chronic kidney disease - Li, Ting-Ting; Wen, Li-Ying; Meng, Sha-Sha; Li, Yu-Sang; Tang, He-Bin (Frontiers in Pharmacology, 2025)
BackgroundGynura procumbens (Lour.) Merr. is a plant used in traditional Chinese medicine that reduces hepatotoxicity, relieves kidney discomfort, and has anti-inflammatory and antioxidant properties. MethodsWe aimed to explore the mechanisms underlying the therapeutic effects of an ethanol extract from G. procumbens stems (EEGS) and selected metabolites on kidney injury and renal anemia associated with chronic kidney disease (CKD). An adenine-induced rat CKD model was used to elucidate the effective mechanism of EEGS and selected metabolites to correct renal anemia.ResultsThe results showed that treatment with EEGS reversed abnormal changes in the blood indicators, including hemoglobin, red blood cells, serum erythropoietin (EPO), and creatinine levels. Moreover, EEGS inhibited xanthine oxidase (XOD) activity in vitro, significantly inhibited liver XOD activity, and reduced intrahepatic inflammatory infiltration. Analysis of the pathological changes revealed that EEGS treatments resulted in reduced renal tubular apoptosis, decreased a number of crystals, a narrowed tubular lumen, and attenuated tubular fibrosis. Immunohistochemical staining revealed that EEGS significantly ameliorated the adenine-induced abnormal changes in the expression of related proteins, including β-catenin, COX-2, HIF-2α, and EPO, in the rat kidney tissues. Among the selected EEGS metabolites, the combined effect of chlorogenic acid and trans-p-coumaric acid was superior to that of either compound alone.ConclusionThese results suggest that EEGS and selected metabolites can effectively correct renal anemia in CKD rats by inhibiting XOD activity, reducing inflammation, and alleviating renal injury.